Modelagem geoestatística de um reservatório carbonático: um exemplo do pré-sal brasileiro - Medeiros, Matheus Edson Mendes (2024)
A hydrocarbon reservoir is a rock formation that harbors oil and/or natural gas, vital energy resources for modern society. The Barra Velha Formation, a pre-salt formation in the Santos Basin, encompasses the most prolific oil reservoirs in Brazil. These reservoirs are highly heterogeneous in terms of their depositional and diagenetic characteristics. The central objective of this research is to construct a three-dimensional facies model of the Berbigão field, located in deep waters of the Santos Basin, and identify zones of higher reservoir quality. To achieve this purpose, seismic and well data provided by the National Agency of Petroleum, Natural Gas, and Biofuels (ANP) were utilized to comprehensively understand the characteristics of the studied reservoir.Using various tools associated with seismic interpretation, the horizons of the Itapema, Barra Velha 300, 200, and 100 formations were identified. Some typical pre-salt seismic facies such as build-ups, mounds, and carbonate platforms were interpreted. Additionally, geological faults were mapped, allowing the construction of the structural model of the study field. From this model, a grid mesh was created to represent the stratigraphic heterogeneities, enabling the generation of the reservoir facies model. Three main facies were identified and distributed across the grid: Porous (46%), Medium Porous (36%), and Closed (18%). The most representative zones of the field exhibit a higher occurrence of porous and medium porous facies, especially in productive areas. These facies were correlated with pre-salt petrographic facies, including arbustiform and arborescent stromatolites, grainstone, shrubby, spherulitic, laminite, and crenulated laminite.The primary reservoir zones are located in structural highs delimited by faults with divergent dips, highlighting the influence of geological structures on facies distribution and reservoir quality. The developed three-dimensional facies model represents the heterogeneities of the carbonate reservoir in the Berbigão Field and provides valuable information for flow simulators. Therefore, the results of this research can assist in field management, decision-making, and consequently, enhance production recovery factor and extend the field's lifespan more efficiently.